LANDSCAPE-BIOTOPICAL VARIABILITY OF EGGS OF MEDITERRANEAN GULL IN STAVROPOL REGION - Mikhail Pavlovich Ilyukh (Наука. Инновации. Технологии)
Analysis of landscape-biotopical variability of eggs of mediterranean gull Larus melanocephalus reveal reliable difference oomorphometrical parameters in diverse geographical conditions, that evidence on territorial heterogeneous and separate of population given species gull in region.